B‐RAIL: UML to B Transformation in Modeling a Level Crossing - Boulanger, Jean‐Louis (Formal Methods Applied to Complex Systems: Implementation of the B Method, 2014)
This chapter considers level crossings, which constitute a critical sub‐system. It proposes a modeling methodology based on the pairing of a semi‐formal method, unified modeling language (UML), and a formal method, the B method, to provide the rigor needed when designing critical systems. The chapter begins with a brief presentation of the issues associated with level crossings, and a rapid presentation of UML notation. It covers the different stages of our methodology point by point. The chapter highlights three considerations: risk analysis during the system design phase allows us to guarantee traceability throughout the whole process; UML notation is suitable for use in formalizing complex systems and for safety requirements; the importance of highlighting requirements and traceability throughout the production cycle. The aim of the B‐RAIL project is to define a methodology for the development of rail transport systems.